Partisipasi Masyarakat Pesisir pada Program Pasar Segoro sebagai Bentuk Pemberdayaan Masyarakat oleh Komunitas Ngayom Jagad di Desa Campurejo Kecamatan Panceng Kabupaten Gresik - Salwa Hani'ah Nabilah; Ali Yusuf (J+PLUS UNESA, 2026)
This study aims to describe the forms of coastal community participation in the Pasar Segoro program and analyze its contribution to local community empowerment. The research was conducted in Campurejo Village, Panceng District, Gresik Regency using a qualitative approach. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation. Data analysis was conducted thematically to understand community participation in various stages of the program. The results showed that coastal communities actively participated in the planning, implementation, utilization, and evaluation stages of the Pasar Segoro program. This participation was reflected through community involvement as MSME actors, program organizers, supporters, and preservers of local culture. The Pasar Segoro program not only provided economic impacts but also strengthened social solidarity, improved community capacity, and built collective awareness of regional potential among coastal communities. Therefore, Pasar Segoro represents a community-based empowerment model capable of integrating economic, social, and cultural aspects in coastal community development.